2021
DOI: 10.3389/fpsyg.2021.729790
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Depressive Symptoms Among Chinese Older Adults: The Mediation and Suppression Effects of Social Capital

Abstract: Exploring the social factors of mental health among older adults has become a hot topic. This study aimed to examine the relationships between internet use, social capital and depressive symptoms in older adults. Our data were derived from a sample of 6,840 respondents aged 60 and over in the 2018 wave of the China Family Panel Studies. The ordinary least square (OLS) regression results showed that both Internet use characteristics (including access, emotional activities, and online time) and social capital co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Finally, this research theoretically extends the application scenario of social capital. As an important social resource for employees ( 57 ), social capital is an important factor affecting job satisfaction ( 50 ). From the external perspective, we found that mental health have effect on the social capital and we further found that social capital is a bridge between mental health and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, this research theoretically extends the application scenario of social capital. As an important social resource for employees ( 57 ), social capital is an important factor affecting job satisfaction ( 50 ). From the external perspective, we found that mental health have effect on the social capital and we further found that social capital is a bridge between mental health and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents of this survey are Chinese residents. The baseline survey of CFPS was initiated in 2010 and followed by four rounds of tracking surveys in 2012, 2014, 2016, and 2018, with samples covering 25 provinces/cities/autonomous regions in China ( 57 ). After excluding observations with missing data and respondents with no income, the final sample was restricted to 6,741 observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, they may be affected by Internet use, as previous research has suggested that online time is negatively associated with mental health. [ 29 ] A Chinese cross-sectional self-report survey suggested that psychological disturbances were associated with daily online time. [ 30 ] Review studies have suggested that Internet use impacts students’ health-promoting and health-threatening behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, another line of research has revealed the positive effect of Internet use on mental health. The Internet can be useful in reducing mental health problems, including loneliness, by improving existing relationships and providing opportunities to form new ones ( Valkenburg and Peter, 2007 ; Li and Yang, 2021 ). In particular, when the Internet is used for social communication, it is correlated to lower levels of loneliness among the older population ( Sum et al, 2008 ; Erikson and Johnson, 2011 ).…”
Section: Introductionmentioning
confidence: 99%